2010
DOI: 10.1088/0029-5515/50/2/025006
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of nitrogen plasmas with tungsten

Abstract: Abstract.The use of nitrogen seeding to reduce the edge plasma temperature has recently been successfully applied in ASDEX Upgrade. While the plasma performance was significantly improved compared to other seeding species like Ar or Ne, questions remained as to the interaction of nitrogen with a tungsten first wall. In particular the formation of thick tungsten nitride layers with reduced melting temperature and increased physical sputtering was a concern. Therefore dedicated laboratory experiments have been p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 25 publications
6
75
2
Order By: Relevance
“…Nitrogen plasma exposure was performed with a working pressure of 0.25 Pa applying a gas flow of 50 sccm N 2 gas. For these conditions it was shown that N 2 + is the dominant ion species [6,7]. It contributes about 85 % to the total ion flux with minor contributions from N 3 + and N + ions ( 5-10 % each) [7].…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Nitrogen plasma exposure was performed with a working pressure of 0.25 Pa applying a gas flow of 50 sccm N 2 gas. For these conditions it was shown that N 2 + is the dominant ion species [6,7]. It contributes about 85 % to the total ion flux with minor contributions from N 3 + and N + ions ( 5-10 % each) [7].…”
Section: Methodsmentioning
confidence: 97%
“…For these conditions it was shown that N 2 + is the dominant ion species [6,7]. It contributes about 85 % to the total ion flux with minor contributions from N 3 + and N + ions ( 5-10 % each) [7]. The ion flux of the main species was about 410 18 N 2 + /m 2 s [7], which resulted in a total N fluence of about 1.510 22 N/m 2 for 30 min plasma exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Such copper interlayers have been used earlier in our laboratory to avoid peeling of magnetron-sputtered W films [38]. Fig.…”
Section: Effect Of Copper Interlayermentioning
confidence: 99%
“…Different from hydrogen or noble gases, N is retained in the walls by forming compounds such as tungsten nitrides [3]. On the other hand, N does not form layers on top of the original wall material and the diffusion of N in tungsten is negligible below 800 K [4].…”
Section: Introductionmentioning
confidence: 99%